UJI COBA BEBERAPA KOMBINASI KOMPOSISI PAKAN TRENGGILING (Manis javanica Desmarest, 1822) DI PENANGKARAN - Anita Rianti; Novriyanti Novriyanti; Mariana Takandjandji (Jurnal Penelitian Hutan dan Konservasi Alam, 2017)
ABSTRACTCaptive breeding is one of the alternative solution to reduce the extinction of pangolin (Manis javanica Desmarest, 1822). This research was aimed to determine the feeding intake and the growth of the pangolin body through the provision of alternative feeding from agricultural wastes and rotten woods. The research was conducted at Multi Jaya Abadi Captive Breeding, located in Medan North Sumatra. Four pangolins were used as material for this study and the observation was done for 14 days. The pangolins were treated with four types of feeding treatments, i.e. A (mixture of rice bran, corn flour and kroto), B (mixture of rice bran, corn flour, and worm), C (mixture of rice bran, corn flour, and cricket), and D (mixture of rice bran, corn flour, and termites). Of the four treatments, feeding alternative of D was the most preferred by pangolin, followed by alternatives A, B and C. This result showed that pangolin in the captive breeding in Medan prefer feeding termites (24.24%), then followed by kroto (20.97%), worms (10.56%), and crickets (9.17%).Key words: Agricultural waste, captive breeding, feeding alternative, pangolin.ABSTRAKSalah satu alternatif yang diharapkan untuk mengatasi punahnya trenggiling, yakni melalui penangkaran. Penelitian ini bertujuan untuk mengetahui konsumsi pakan dan pertumbuhan badan trenggiling melalui penyediaan pakan alternatif dari limbah pertanian dan kayu lapuk. Penelitian dilakukan di Multi Jaya Abadi, yang berlokasi di Medan, Sumatera Utara. Empat individu trenggiling merupakan materi penelitian yang digunakan selama 14 hari pengamatan dan diberi empat perlakuan pakan, yakni A = dedak padi+tepung jagung+kroto; B = dedak padi +  tepung jagung + cacing; C = dedak padi + tepung jagung + jangkrik; dan D = dedak padi + tepung jagung + rayap. Empat perlakuan kombinasi pakan tersebut, kombinasi pakan D paling disukai oleh trenggiling, diikuti dengan kombinasi pakan A, B dan C. Hasil penelitian membuktikan bahwa trenggiling di penangkaran Medan lebih menyukai pakan rayap (24,24%), diikuti oleh kroto (20,97%), cacing (10,56%), dan jangkrik (9,17%).Kata kunci: Limbah pertanian, penangkaran, jenis pakan alternatif, trenggiling.